Enhanced Local Magnetization by Interface Engineering in Perovskite‐Type Correlated Oxide Heterostructures. Issue 3 (2nd January 2015) - Huijben, Mark; Liu, Yaohua; Boschker, Hans; Lauter, Valeria; Egoavil, Ricardo; Verbeeck, Jo; te Velthuis, Suzanne G. E.; Rijnders, Guus; Koster, Gertjan
<x xml:space="preserve">Abstract</x> Elimination of a magnetic dead‐layer at the LSMO/STO interface is achieved by interface engineering through incorporation of a single La0.33Sr0.67O layer. Controlled growth of interfacial atomic stacking in combination with local magnetic probing by polarized neutron reflectometry enables controlled interface engineering and results in optimal interfacial magnetization in perovskite‐type correlated oxide heterostructures. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>